HUBUNGAN POLA MAKAN DAN STATUS GIZI TERHADAP KADAR HEMOGLOBIN MAHASISWI FAKULTAS KESEHATAN UNIVERSITAS MUHAMMADIYAH GRESIK. - Yasirotul Hikmah; Dwi Novri Supriatiningrum; Amalia Rahma (Universitas Muhammadiyah Gresik, 2023)
Indonesia has health problems that still often occur, especially in women of childbearing age, namely a lack of red blood cells or can be called anemia caused by nutrient intake. The problem of anemia, especially in women of childbearing age, has a bad impact on the sufferer and the generation to be born. This study aims to determine the relationship between diet and nutritional status to hemoglobin levels in college of the Faculty of Health, University of Muhammadiyah Gresik. The type of research is obvarsional analytics with a cross sectional approach. A total of 85 samples were taken using purposive sampling techniques. Data analysis using the spearman rank test, dietary data collection was carried out day food konsumtionbsurvey with repeated 24-h-recall and food freques method. the data of nutritional status was determined by measurment of body mass index, hemoglobin levels were obtained by hemoglobin examination using digital easy touch. The results of the spearman rank correlation test on the dietary intake variable showed a p-value result of <0.05 which means that there was a relationship of diet to hemoglobin levels, and in the nutritional status variable, it shows a p-value result of >0.05 which means that there is no relationship of nutritional status to hemoglobin levels. There is a relationship between diet and hemoglobin levels, contrasts with food intake, the correlation of nutritional status and hb level showed not significant (p-value >0,05). there is no relationship between nutritional status and hemoglobin levels in students of the Faculty of Health, University of Muhammadiyah Gresik.